The effectiveness and sustainability of peer support interventions for persons living with HIV: a realist synthesis. Issue 2 (20th February 2023) - Han, Shuyu; Zhang, Yizhu; Yang, Xianxia; Chai, Xinru; Guo, Jinzheng; Zhang, Lili; Shao, Ying; Ma, Jianhong; Li, Ke; Wang, Zhiwen
Abstract : Background: Peer support is an important supplement to medical resources for persons living with HIV (PLHIV). However, previous studies have shown mixed results about intervention effects. It is necessary to explain the mechanism of peer support interventions' effectiveness and sustainability to help design more valid peer support interventions. Objective: To identify and explain the mechanisms that drive the effectiveness and maintain the sustainability of peer support interventions. Methods: A preliminary theoretical framework was developed through a scoping review of the grey literature and international project frameworks in five professional websites. We then refined the framework by systematically searching evidence in databases including PubMed, EMBASE, Web of Science, ProQuest, CINAHL, CNKI and Wanfang. Qualitative methods were used to generate codes and themes relating to the studies' context, mechanisms and outcomes. We checked chains of inference (connections) across extracted data and themes through an iterative process. Results: A total of 6345 articles were identified, and 52 articles were retained for final synthesis. The refined theoretical framework presents five areas of peer support, including informational support, instrumental support, emotional support, affiliational support and appraisal support; five types of outcomes that peer support can improve for PLHIV, including physiological outcomes, psychological outcomes, behavioural outcomes, cognitive outcomes and social outcomes; the effectiveness mechanism coding system from peer volunteers and the relationship between peer volunteers and PLHIV; and the sustainability mechanism coding system in terms of peer volunteers, PLHIV and study context. Conclusions: Given that peer support has huge potential human resources, that is, all the qualified PLHIV, irreplaceable advantages in dealing with barriers to HIV-related discrimination and potential comprehensive benefits for PLHIV, it is necessary to develop and organise more peer support projects for PLHIV. Our study highlights that the expansion of peer support projects should be based on their effectiveness and sustainability. PROSPERO registration number: CRD42022339079.